Analysis of methods and means of improving the reliability of elements of relay protection - Бунько, Василь Ярославович (Technology audit and production reserves, 2015)
This paper analyzes the methods of selecting the number of sets of relay protection and automation (RPA) and reservation schemes for the protected object. The calculation procedure of parameters of reliability of RPA systems for three types of protecting objects that allow grounding schemes of reservation of RPA systems and providing the required level of reliability of electricity supply facilities. It is developed the model for the RPA functioning of modern element base, which revealed the following components performance of relay protection systems in modern terms as software reliability, security from external electromagnetic and other influences, and the human factor. It is proposed the scheme of accounting influencing factors (parameter of short circuit flow(SC), the effect of staff ("human factor"), uniqueness of recovery), thus allow founding dependence of resulting indicators of reliability from influencing factors and assess the impact of factors on the results of reliability calculations. The features of the model are taken into account when calculating the reliability of hardware of RPA systems and reliability indexes of relay protection for three objects: power lines, busbars and power transformer. This will allow justifying and choosing the schemes of reservation of RPA systems, which greatly increase the reliability of electricity supply system in general.